2021
DOI: 10.1002/adfm.202009619
|View full text |Cite
|
Sign up to set email alerts
|

Partial Coated Stem Cells with Bioinspired Silica as New Generation of Cellular Hybrid Materials

Abstract: The manipulation of cell surfaces in anchorage-dependent cells can help overcome difficulties presented during cell handling and application. Silica-based protective mechanisms existing in free-floating microorganisms may be used as inspiration for sustaining human cell survival in suspension. Gathering on this, herein human adipose-derived mesenchymal stem cells (hASCs) are partially coated with a hard silica layer that operates as a supporting platform for individual cells in suspension. Inspired by the orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…It is important to keep the cell structures intact during the whole 3D printing process. Earlier studies have shown the effect of coating on protecting the cells from the damage that occurs due to the stresses generated during the printing process [ 121 , 122 ]. In a study, adipose derived mesenchymal stem cells were partially coated with silica, inspired by biosilicification [ 122 ].…”
Section: 3d Printed Polymeric Biomaterialsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is important to keep the cell structures intact during the whole 3D printing process. Earlier studies have shown the effect of coating on protecting the cells from the damage that occurs due to the stresses generated during the printing process [ 121 , 122 ]. In a study, adipose derived mesenchymal stem cells were partially coated with silica, inspired by biosilicification [ 122 ].…”
Section: 3d Printed Polymeric Biomaterialsmentioning
confidence: 99%
“…Earlier studies have shown the effect of coating on protecting the cells from the damage that occurs due to the stresses generated during the printing process [ 121 , 122 ]. In a study, adipose derived mesenchymal stem cells were partially coated with silica, inspired by biosilicification [ 122 ]. Individual cells were coated with a hard silica layer (called backpack) to provide them with a supporting platform [ 122 ].…”
Section: 3d Printed Polymeric Biomaterialsmentioning
confidence: 99%
See 3 more Smart Citations